2012
DOI: 10.2752/175174212x13414983522035
|View full text |Cite
|
Sign up to set email alerts
|

Homemaking, Homebuilding, and the Significance of Place and Kin in Rural Kyrgyzstan

Abstract: In rural Kyrgfyzstan, homes built by their owners house multigenerational families and are filled with objects that have been bought, made, acquired, and received. Many of them come as gifts cementing alliances with other families through marriage. This article discusses how kelin (daughtersin-law) and their families negotiate aspects of themselves and their relationships through interactions with these objects and places of domesticity. Many studies of Central Asia identify patrilineage and land as major fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The parents' generation bases its claim on the understanding of family as it is socially practiced in Kyrgyzstan. Multi-generational families are the ideal (Reynolds, 2012) and a statistically proven reality. They come about because adult sons in particular remain living in their parents' household.…”
Section: Introduction -Parent Generation's Authoritymentioning
confidence: 99%
“…The parents' generation bases its claim on the understanding of family as it is socially practiced in Kyrgyzstan. Multi-generational families are the ideal (Reynolds, 2012) and a statistically proven reality. They come about because adult sons in particular remain living in their parents' household.…”
Section: Introduction -Parent Generation's Authoritymentioning
confidence: 99%
“…In this analysis of the built environment in Viștea, I intend to contribute to literature on the material culture studies of the home. A wide range of research revealed that domestic objects and home decorations constitute a dynamic relationship between remembering and forgetting and illuminate notions of kinship and gender as well as local symbolic categories (Carsten and Hugh Jones 1995, Empson 2006, Grossman 2015, Iuga 2011, Reynolds 2012. Following Levi-Strauss, studies considered the house as a "corporate body holding an estate made up of both material and immaterial wealth" (Levi-Strauss 1983: 174) and explored the relations between the fabric of social organisation, local identity and shifting idioms of household (Pine 1996(Pine , 2002.…”
Section: Introductionmentioning
confidence: 99%